Субклінічний синдром Кушінга та його значення в ендокринології та хірургії надниркових залоз - Черенько, С. М.; Товкай, О. А.; Щекатурова, Л. В.; Третяк, О. Е. (Clinical Endocrinology and Endocrine Surgery, 2014)
Comprehensive analysis of various clinical variants and prevalence of subclinical Cushing’s syndrome was done in the article as well as its differences with classical course of disease. On the basement of literature and own clinical data (622 patients with adrenal masses who were underwent adrenalectomy, 324 patients with metabolic syndrome and 578 patients with suspected primary hyperaldosteronism) the rate of hidden hypercortisolaemia was studied. Involution of symptoms after adrenalectomy was followed up. Rele The topic was illustrated by literature review and own experience of 129 patients. The relevant diagnostic approach was proposed with emphasis on 1 mg overnight dexametasone test as most reliable screening analysis.